2022
DOI: 10.1007/s11145-022-10265-7
|View full text |Cite
|
Sign up to set email alerts
|

Task-oriented reading efficiency: interplay of general cognitive ability, task demands, strategies and reading fluency

Abstract: The associations among readers’ cognitive skills (general cognitive ability, reading skills, and attentional functioning), task demands (easy versus difficult questions), and process measures (total fixation time on relevant and irrelevant paragraphs) was investigated to explain task-oriented reading accuracy and efficiency (number of scores in a given time unit). Structural equation modeling was applied to a large dataset collected with sixth-grade students, which included samples of dysfluent readers and tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…However, there are significant differences in reading comprehension ability in more detail when tested with the three items of types of memory, comprehension, and application. The findings of this study are reinforced by the findings of previous studies which confirmed that static text can be read more quickly than the dynamic scrolling type, but the reading comprehension ability resulting from the two types is not very significant (Hautala et al, 2022;Ravand & Robitzsch, 2018).…”
supporting
confidence: 78%
See 2 more Smart Citations
“…However, there are significant differences in reading comprehension ability in more detail when tested with the three items of types of memory, comprehension, and application. The findings of this study are reinforced by the findings of previous studies which confirmed that static text can be read more quickly than the dynamic scrolling type, but the reading comprehension ability resulting from the two types is not very significant (Hautala et al, 2022;Ravand & Robitzsch, 2018).…”
supporting
confidence: 78%
“…Cognitive load is divided into several types, namely intrinsic, foreign, and close (Albus & Seufert, 2023;Hautala et al, 2022). Intrinsic is the countryside of the material being studied such as material content that has a high level of difficulty.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Graesser (2016) affirms that technology can work as auto tutor to motivate students to read. Similarly, Hautala et al (2022) assert that assistive technology helps students to acquire cognitive skills, which are required to improve their reading performance since technology assists them to improve attention, visual and auditory processing, and short-term and long-term memory. In similar findings, Cauley et al (2019) assert that TTS technology helps students improve vocabulary, reading comprehension, and reading fluency.…”
Section: Discussion and Findingsmentioning
confidence: 99%
“…Automaticity and repeated reading exercises can also help students to achieve fluency while interacting in predicting reading comprehension (Kieffer & Christodoulou, 2020;Swain et al, 2017). The cognitive skills that students need to improve their reading performance include attention, visual and auditory processing, sensory integration, and short-term and long-term memory (Hautala et al, 2022;Wang et al, 2003). According to Hautala et.al, students can develop their reading cognitive abilities when they monitor their cognitive processes.…”
Section: Introductionmentioning
confidence: 99%